Destinos turísticos e populações nativas: experiência e narrativas de mudança social - Lopes, Francisco Willams Ribeiro (2019)
This Doctorate dissertation analyzes processes of social change unfolding from the relation between local fishermen populations and touristic activity in the coastal village of Cumbuco, in the state of Ceará, Brazil. The aim is to present how native dwellers of Cumbuco think and act in regards to practices of mobility and interventions conducted on behalf of tourism. The investigation was carried out with a qualitative-based methodology– comprised of field research, observation and interviews – from 2014 to 2018, and shows that the figuration of Cumbuco as a touristic site derived from processes of mobility and change, lived by native dwellers over the last decades. The narratives of social change shared by local fishermen highlighted the public and private sector interventions aiming to increase the coast’s value for summer holidays, the creation of infrastructure for the flow of Brazilian and foreign visitors, and the promotion of water sports practice. Furthermore, both the construction of a new branding image for Ceará, which was associated with the Sun, the sea, rafts and idyllic places, and the public policies framing tourism as a strategy of economic development, integrated the repertoire of interventions that boosted changes in the locality. The dissertation draws conclusions that may be tested in other contexts, such as the increased influx of visitors, goods, services and capital set forth by touristic activity, which has expanded the relations of interdependence among agents who promote tourism and local populations, influencing the territory and its activities of production, leading not only to transformations in traditional features, but also in reinforcing traces of the so-called local culture. Besides, it shows that sites oriented towards tourism are influenced by the global dynamics of people, goods and capital flow, which produce and reproduce the figuration of such localities as ‘touristic destinations’, and contribute to the formation of translocalities in the contemporary world.